2019
DOI: 10.1609/aaai.v33i01.33012817
|View full text |Cite
|
Sign up to set email alerts
|

Disjunctive Normal Form for Multi-Agent Modal Logics Based on Logical Separability

Abstract: Modal logics are primary formalisms for multi-agent systems but major reasoning tasks in such logics are intractable, which impedes applications of multi-agent modal logics such as automatic planning. One technique of tackling the intractability is to identify a fragment called a normal form of multiagent logics such that it is expressive but tractable for reasoning tasks such as entailment checking, bounded conjunction transformation and forgetting. For instance, DNF of propositional logic is tractable for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Forgetting was recently extended to multi-agent modal logics [27]. It is showed that computing forgetting results of formulas in disjunctive normal form is feasible in polynomial time [28]. In addition, practical uniform interpolation systems for modal logic were developed [29].…”
Section: Forgettingmentioning
confidence: 99%
“…Forgetting was recently extended to multi-agent modal logics [27]. It is showed that computing forgetting results of formulas in disjunctive normal form is feasible in polynomial time [28]. In addition, practical uniform interpolation systems for modal logic were developed [29].…”
Section: Forgettingmentioning
confidence: 99%